CORRELATION BETWEEN READING STRATEGIES AND READING MOTIVATION TO READING COMPREHENSION OF THE THIRD SEMESTER STUDENTS AT THE ENGLISH EDUCATION STUDY PROGRAM OF STAIN PALANGKA RAYA - Erliana, Santi (English Department of Faculty of Tarbiyah and Teachers Training, 2015)
Experts believe it takes more than just reading aloud or read word by word to achieve the comprehension level since reading takes the occurrence of interaction between knowledge existing in a learnerâs mind (prior knowledge) and the new knowledge from the information being read in the text, takes the use of strategies in reading, and the readersâ awareness in monitoring their comprehension and in using appropriate strategies to deal with their problems in comprehending texts. Their studies recommend readers to utilize strategies in reading and to have motivation in learning reading to achieve better comprehension. The present study aims at examining the correlation between reading strategies and reading comprehension, correlation between reading motivation and reading comprehension, correlation between combinations of reading strategies and reading motivation toward reading comprehension. The study used quantitative design, particularly correlational. 46 third semester students at the academic year 2014/2015 were taken as the sample of the study. The data were taken from reading strategies and reading motivation questionnaires and reading achievement test. The finding indicates the significant simultaneous correlation between reading strategies and reading motivation toward reading comprehension of the third semester students. The finding recommends the utilization of strategies in reading and to build reading culture for the students, the teaching of reading using strategy instruction which provide opportunities for the students to utilize reading strategies and to have more positive response toward reading for the lecturers, and Classroom Action Research using strategy instruction for better reading comprehension for the future researcher.Â